2011
DOI: 10.1161/circresaha.110.225201
|View full text |Cite
|
Sign up to set email alerts
|

The Inotropic Peptide βARKct Improves βAR Responsiveness in Normal and Failing Cardiomyocytes Through G βγ -Mediated L-Type Calcium Current Disinhibition

Abstract: Rationale The Gβγ-sequestering peptide βARKct derived from the G-protein coupled receptor kinase 2 (GRK2) carboxy-terminus has emerged as a promising target for gene-based heart failure (HF) therapy. Enhanced downstream cAMP signaling has been proposed as the underlying mechanism for increased β-adrenergic receptor (βAR) responsiveness. However, molecular targets mediating improved cardiac contractile performance by βARKct and its impact on Gβγ-mediated signaling have yet to be fully elucidated. Objective We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
2
2

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 60 publications
3
35
2
2
Order By: Relevance
“…In vivo cardiac-targeted PRAS40 expression in normal mouse hearts was obtained by using tail vein injection of an AAV9 harboring the PRAS40 gene or PRAS40TA mutant driven by a cardiomyocyte-specific CMV-MLC2v0.8 promoter as previously described (34).…”
Section: Methodsmentioning
confidence: 99%
“…In vivo cardiac-targeted PRAS40 expression in normal mouse hearts was obtained by using tail vein injection of an AAV9 harboring the PRAS40 gene or PRAS40TA mutant driven by a cardiomyocyte-specific CMV-MLC2v0.8 promoter as previously described (34).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, why does the phenotype of GRK2 deletion differ profoundly from the recently characterized EC coupling phenotype after ␤ARKct overexpression 25 ? In the latter, the only change of EC coupling that could be observed was ␤ARKct-mediated relief of G ␤␥ -induced inhibition of LTCC, supporting the earlier idea that ␤ARKct mediates its beneficial effects via G ␤␥ scavenging rather than GRK2 inhibition.…”
Section: Article See P 2108mentioning
confidence: 99%
“…Most studies-including studies with bARKct expression in HF pigs-have shown a reversal of bAR dysfunction including receptor upregulation and a normalization of signaling; however, no doubt, there are effects of the bARKct that go beyond resensitization of cardiac bARs and these effects are currently being explored by us and others. 54,55 Adrenal GRK2 as a novel HF gene therapy target As discussed above, HF is associated with enhanced catecholamine secretion from the adrenal glands because of a 2c AR desensitization by GRK2. This central role in the critical elevation of plasma catecholamine levels contributing to HF development and progression renders adrenal GRK2 an interesting target for HF treatment.…”
Section: Targeting Grk2 By Gene Therapy For Hf J Reinkober Et Almentioning
confidence: 99%
“…59 This observation suggests that the contractile effects of bARKct might be because of inhibition of additional G bg pathways other than a bAR-mediated effect, although this has yet to be proven experimentally. In addition, Völkers et al 54 recently demonstrated that a part of the positive inotropic effects of bARKct is attributable to the disruption of G bg -mediated inhibition of cardiac L-type Ca 2+ channels, as bARKct expression in myocytes significantly improved Ca 2+ cycling via augmentation of the L-type Ca 2+ channel current. Another bAR-independent effect of the bARKct in the heart appears to be reversal of GRK2-mediated insulin resistance in myocytes, 55 which definitely needs to be explored as contributing to the therapeutic effects of GRK2 inhibition in HF.…”
Section: Targeting Grk2 By Gene Therapy For Hf J Reinkober Et Almentioning
confidence: 99%